A Survey of Pyridoxal 5′-Phosphate-Dependent Proteins in the Gram-Positive Model Bacterium Bacillus subtilis - Richts, Björn; Rosenberg, Jonathan; Commichau, Fabian M. (Frontiers in Molecular Biosciences, 2019)
The B6 vitamer pyridoxal 5’-phosphate (PLP) is a cofactor for proteins and enzymes that are involved in diverse cellular processes. Therefore, PLP is essential for organisms from all kingdoms of life. Here we provide an overview about the PLP-dependent proteins from the Gram-positive soil bacterium Bacillus subtilis. Since B. subtilis serves as a model system in basic research and as a production host in industry, knowledge about the PLP-dependent proteins could facilitate engineering the bacteria for biotechnological applications. The survey revealed that the majority of the PLP-dependent proteins are involved in metabolic pathways like amino acid biosynthesis and degradation, biosynthesis of antibacterial compounds, utilization of nucleotides as well as in iron and carbon metabolism. Many PLP-dependent proteins participate in de novo synthesis of the cofactors biotin, folate, heme and NAD+ as well as in cell wall metabolism, tRNA modification, regulation of gene expression, sporulation and biofilm formation. A surprisingly large group of PLP-dependent proteins (34%) belong to the group of poorly characterized proteins. This review underpins the need to characterize the PLP-dependent proteins of unknown function to fully understand the ‘PLP-ome’ of B. subtilis.